Gallbladder Wall Thickness as a Non-Invasive Tool for Prediction of Esophageal Varices in Patients with Hepatitis C Related Chronic Liver Disease - Munir Ahmed; Maliha Aziz; Shahzad Riyaz; Mohammad Salih; Rashed Nazir; Muslim Atiq (Pakistan Journal of Medical Research)
Background: The early identification of esophageal varices in patients with chronic liver disease (CLD) is important in order to mitigate the risk of variceal hemorrhage and mortality.  Many noninvasive predictors have been studied for esophageal varices (EVs).